LEIRIA & OESTE: AN ECOSYSTEM THAT CHALLENGES CONVENTIONS AND REINVENTS THE FUTURE - Duarte de Almeida, I.; da Silva, Agostinho; C. Rabadão (11th International Conference on Intercultural Mediation and Social Intervention – “Territories, Municipalities, Networks, and Partnerships: Intercultural Mediation and Social Intervention, 2024)
This article reports innovative ecosystem services' scaling-up processes using service-dominant logic. The study identifies key social, economic, and environmental barriers and drivers in Portugal's Leiria & Western Region (LWR). Based on the findings, an innovative conceptual framework identifies pilot projects to promote regional development. Pilot projects' scale-up to improve municipalities' socio-economic dimensions will be determined by their impact, local adaptation, resource alignment, and value resonance.